The Economic Behavior of Coastal Community in Bangil, Pasuruan Regency - Mochamad Taufiq; Dies Nurhayati; Sugeng Pradikto; Nunuk Khomariyah (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
Coastal communities often face a tension between the need to manage limited and fluctuating income and the growing influence of consumption-oriented lifestyles. This study examines the economic behavior of the Bangil coastal community in Kalianyar Village, Pasuruan Regency, focusing on three dimensions: economic rationality, economic morality, and lifestyle. A qualitative case-oriented approach was employed with nine local fishermen selected through purposive sampling. Data were collected from March to July 2025 through in-depth interviews, direct observation, and documentation, while source triangulation was used to strengthen data credibility. The findings indicate that community members demonstrate rational economic behavior when prioritizing essential needs, considering product quality, consulting family members on major purchases, and reinvesting income in productive activities. However, these practices are accompanied by limited saving habits, weak separation between household and business finances, and reliance on borrowing when income is insufficient. Economic morality is primarily developed through family-based education, particularly through parental guidance on saving, responsible spending, and financial discipline, although inconsistent parental practices may weaken these habits among children. Lifestyle is strongly influenced by social surroundings, consumer trends, fashion, and technological developments, which can encourage spending based on wants rather than necessities. The study concludes that coastal economic behavior emerges from the interaction of rational decision-making, family economic education, and lifestyle pressures. Strengthening financial literacy, disciplined saving, responsible consumption, and family-based economic education is therefore important for improving household financial resilience in coastal communities.